Analisis Penetapan Harga Dan Pengaruhnya Terhadap Volume Penjualan Pada Bir Pletok (Studi Kasus pada UKM Bir Pletok Bang Isra, Jakarta) - Sri Hartini; Sumihar L Tobing; Imas Wildan Rafiqah (Fakultas Pertanian Universitas Borobudur, 2021)
ABSTRACTThis study aims to determine the effect of the variable price of 250 ml bottle birpletok, the 600 ml bottle bir pletok price variable, and the bir pletok productioncost to the bir pletok sales volume. This research was conducted at UKM BirPletok Bang Isra, Jakarta. The data obtained is secondary data in the form ofprice data, production costs and sales volume. The data analysis method used inthis study is multiple linear regression analysis. The results showed that thevariable price of 250 ml bottle bir pletok and the 600 ml bottle bir pletok pricewas not significant to the variable bir pletok sales volume with a significancevalue of 0.860 and 0.865. The results of this study also show that the variable production costs have a significant effect on the variable volume of bir pletoksales with a significance value of 0.000. The variable price of bir pletok, both 250ml and 600 ml bottles, and the variable production costs simultaneously have asignificant effect on the variable sales volume of Bang Isra’ Bir pletok. In thecoefficient of determination, there is an effect of 95.5% of the price andproduction costs on sales volume.Keywords: Sales Volume, Bir Pletok, Price, and Production Cost